A novel design of high performance multilayered cylindrical dielectric lens antenna using 3D printing technology - Belen, Aysu; Gunes, Filiz; Mahouti, Peyman; Palandoken, Merilt (WILEY, 2020)
In this work, design and realization of high performance, low-cost X-band multilayered cylindrical dielectric lens antenna (MLCDLA) is presented using 3D printing technology. Firstly, MLCDLA is designed and simulated in the complete 3D CST microwave studio (MWS) within the X- band as consisting of six layers and being fed through a conventional rectangular waveguide (WR90). These layers are in the form of cylindrical discs having different radii, thicknesses and made of a cheap polylactic acid material. These layers have also varying dielectric constant from 1.2 to 2.7 that are compatible for fused deposition modeling (FDM) based 3D-printing process. Secondly, a prototype of MLCDLA is produced by using a FDM based 3D-printer. 3D printed dielectric lens antenna is measured and a good return loss of almost more than 10 dB within the X-band with a high gain of 16-18 dBi are achieved as compared with the counterpart alternative designs. Thus, it can be concluded that the proposed novel design and prototyping method not only achieves the high radiation performance characteristics along X-band but also is a fast, low-cost, and effective method for prototyping dielectric lens structures for the microwave applications.
Keywords: 3D printer; broadband; high gain; lens antenna; nonuniform lens; HORN; REALIZATION; Computer Science; Engineering